Best Proximity Point Theorems without the P-Property for New Generalized Weakly Contraction Mappings in Partially Ordered Metric Spaces: Aphinat Ninsri, Wutiphol Sintunavarat - Team, Support (Thai Journal of Mathematics, 2018)
In this paper, we define the new concept of a generalized weakly contractive condition for nonlinear nonself-mappings and establish new best proximity point theorems for such mappings with three control functions in partially ordered metric spaces without the P-property. These results generalize the main results of Babu and Leta [1].